Donor-acceptor organic nanostructure based on conjugated polymer for improving visible-light-driven photocatalytic activity towards degradation of dye in aqueous medium - Behere R.P.; Laxmi R.; Gupta N.; Sharma U.; Das S.; Kuila B.K. (My University, 2025)
Conjugated-polymer-based donor-acceptor hybrid nanostructures have been the subject of great interest, mainly due to their potential applications in photovoltaic and other electronic and optoelectronic devices. Here, we have demonstrated a different aspect of these hybrid nanostructures toward efficient photocatalysis in an aqueous medium. The hybrid donor-acceptor nanostructures were prepared by assembling a carboxylic acid-functionalized fullerene molecule (phenyl C-61 butyric acid) (PCBA) on the surface of an amine-functionalized regioregular P3HT nanostructure through acid-base interaction. The efficient photoinduced charge separation and charge transfer in the hybrid material were investigated by steady-state and time-resolved photoluminescence and photocurrent measurements. The photocatalytic activity of the hybrid nanostructure in water under visible light irradiation (using a 20 W white LED bulb) was investigated, and it was found to show 82.5% dye degradation efficiency. To facilitate the reusability of the photocatalyst, a membrane-based dip-photocatalyst was developed from this material, and it shows 87.5% dye degradation efficiency and can be reused multiple times without a significant change in degradation efficiency. © 2022 The Royal Society of Chemistry.